DIGITALISASI HELPDESK LPSE DI BAGIAN PENGADAAN BARANG DAN JASA BANYUWANGI - Fara Abi Shafira; Ahmad Lutfi (Jurnal Advanced Research Informatika, 2023)
IT helpdesk is a system that helps users solve problems. Then, it allows users to troubleshoot, track their issues, and get help regarding services. LPSE in the procurement of services and administration can not be separated form the use of IT. Eelectronic Procurement services in the Goods and services procurement section require an application that can make it easier for agencies to submit probels which is called the Helpdesk. The development method used in designing this system is waterfall, by utilizing the web with the PHP programming language with Apache as a web server and a database using MYSQL. It is hoped that this research can help facilitate technicians in Electronic Procurement Services in the Goods and Services Departement in filing problems of interference or demage.